2021
DOI: 10.1111/aas.13939
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term consequences in critically ill COVID‐19 patients: A prospective cohort study

Abstract: Background COVID‐19 can cause severe disease with need of treatment in the intensive care unit (ICU) for several weeks. Increased knowledge is needed about the long‐term consequences. Methods This is a single‐center prospective follow‐up study of COVID‐19 patients admitted to the ICU for respiratory organ support between March and July 2020. Patients with invasive ventilation were compared with those with high‐flow nasal oxygen (HFNO) or non‐invasive ventilation (NIV) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 35 publications
6
47
5
Order By: Relevance
“…The 6-min walk is a commonly used measure of exercise capacity for patients with chronic lung disease, which evaluates the responses of the pulmonary and cardiovascular systems, systemic and peripheral circulation, neuromuscular units, and muscle metabolism [ 22 , 34 ]. In our study, the distance patients walked in 6 min was longer than expected compared to the previous studies [ 5 , 6 , 8 , 10 , 28 , 29 ]. The walk distance was below the predicted value only in one-third of the patients, only four patients performed reduced exercise capacity assessed as distance below 80% of predicted, and only two patients performed below the LLN.…”
Section: Discussioncontrasting
confidence: 69%
“…The 6-min walk is a commonly used measure of exercise capacity for patients with chronic lung disease, which evaluates the responses of the pulmonary and cardiovascular systems, systemic and peripheral circulation, neuromuscular units, and muscle metabolism [ 22 , 34 ]. In our study, the distance patients walked in 6 min was longer than expected compared to the previous studies [ 5 , 6 , 8 , 10 , 28 , 29 ]. The walk distance was below the predicted value only in one-third of the patients, only four patients performed reduced exercise capacity assessed as distance below 80% of predicted, and only two patients performed below the LLN.…”
Section: Discussioncontrasting
confidence: 69%
“…high-flow nasal cannula or mechanical ventilation) but not with oxygen dependence. However, this association has not been observed in several other studies [ 53 , 58 , 62 , 63 ], including for patients requiring intensive care [ 12 , 63 ].…”
Section: Psychiatric Symptoms and Disordersmentioning
confidence: 76%
“…Some continued experiencing mental consequences that persisted and stayed clinically significant at up to 4 years of follow-up [ 32 ]. Few prospective studies have shown that symptoms of long COVID-19 can persist 3 months [ 87 ], 5 months [ 88 ], 6 months [ 89 , 90 ], and even up to 12 months [ 91 , 92 ] post-hospitalization. Several studies have also shown the presence of psychiatric manifestations post-COVID-19 infection.…”
Section: Psychiatric Sequelae Of Covid-19mentioning
confidence: 99%